Efficacy and Safety of a Combination of Cinnarizine and Dimenhydrinate in the Treatment of Vertigo - Kiran, Dr. Mayuresh; Pawaskar, Mr. Lalit (International Journal of Innovative Research in Medical Science, 2018)
Introduction and Background: Vertigo is a medical condition where a person feels as he/ she or the objects around them are moving when they are stable and not moving. Antihistamines, Calcium antagonists, histamine analogs (eg, betahistine derivatives), diuretics, neuroleptics as well as other psychotherapeutic drugs, corticosteroids agents and hemorheologics can be used for the treatment of Vertigo. Combination of Cinnarizine which is a selective calcium-channel blocker and Dimenhydrinate which is an H 1 antihistaminic drug can be used in combination for the treatment of vertigo. This clinical study was conducted to evaluate the efficacy and safety of combination of Cinnarizine 20 mg and Dimenhydrinate 40 mg in patients of vertigo of age group 18 to 65 years. Methodology: Out of total 216 patients, 168 completed the study. Efficacy assessment was made by analysing the reduction in vertigo symptom score (VSS). Safety assessment was made by analysing the adverse events experienced by the patient or observed by the investigator during trial. Results: Reduction in VSS from 7.277 (baseline) to 3.975 (day 3) and 0.987 (day 5). At visit 2 and visit 3 there was reduction of 45.373 % and 86.426 % in mean VSS score. Conclusion: A combination of Cinnarizine 20 mg and Dimenhydrinate 40 mg is safe and efficacious in the treatment of vertigo.